Utilization of coal bottom ash and fine coconut shell as partial sand replacement in concrete - Mazenan, Puteri Natasya (2019)
Sustainable development and environmental protection have become the key goals of the modern society. Nowadays, huge volumes of coal bottom ash (CBA) are disposed of in coal ash ponds or landfills. On the other hand, the coconut industry is facing disposal problems due to the slow decomposition process of coconut shells which has led to the accumulation of coconut shell piles. Therefore, this study aims to determine the properties of sustainable concrete containing CBA and fine coconut shell (FCS) as partial sand replacement. Normal concrete design with compressive strength of 30 MPa strength at 28 days curing age and a water-cement ratio of 0.50 was used in this study. The percentages of CBA used were 5%, 10%, 15% and 20% while the percentages of FCS used were 2%, 4%, 6% and 8% where its replaced by volume. The slump test was performed to determine the workability of the fresh concrete. The specimens were cured in a water tank for 7, 28, 56 and 90 days before they were tested in terms of compressive strength, splitting tensile strength and water absorption. Design Expert software was used for Response Surface Method (RSM) analysis to determine the optimum percentages of CBA and FCS as partial sand replacement in concrete. CBA and FCS were inserted as factors (input) whereas the results of fresh and hardened concrete from the experimental work were inserted as response (output) in the software in order to determine the optimum percentage. As conclusion, the workability of the concrete decreased with the incorporation of CBA and FCS in concrete while the compressive strength and splitting tensile strength were improved. In addition, the percentage of water absorption increased as both CBA and FCS are capable of absorbing water. It was found that the optimum percentages of CBA and FCS were 10% and 6% respectively. These percentages resulted in the optimum performance of concrete in terms of workability and strength in this study.